CONTROLE DE ð˜šð˜–ð˜™ð˜Žð˜ð˜œð˜” ð˜ð˜ˆð˜“ð˜Œð˜—ð˜Œð˜•ð˜šð˜Œ (l.) PERS. COM APLICAÃ‡Ã•ES DE GLIFOSATO E DALAPON EM REBROTAS COM DIFERENTES ALTURAS - Deuber, Robert; Forster, Reinaldo (REVISTA DE AGRICULTURA, 2020)
CONTROLE DE ð˜šð˜–ð˜™ð˜Žð˜ð˜œð˜” ð˜ð˜ˆð˜“ð˜Œð˜—ð˜Œð˜•ð˜šð˜Œ (l.) PERS. COM APLICAÃ‡Ã•ES DE GLIFOSATO E DALAPON EM REBROTAS COM DIFERENTES ALTURAS